2022
DOI: 10.3389/fonc.2021.663370
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Parametric Magnetic Resonance Imaging-Based Radiomics Analysis of Cervical Cancer for Preoperative Prediction of Lymphovascular Space Invasion

Abstract: BackgroundDetection of lymphovascular space invasion (LVSI) in early cervical cancer (CC) is challenging. To date, no standard clinical markers or screening tests have been used to detect LVSI preoperatively. Therefore, non-invasive risk stratification tools are highly desirable.ObjectiveTo train and validate a multi-parametric magnetic resonance imaging (mpMRI)-based radiomics model to detect LVSI in patients with CC and investigate its potential as a complementary tool to enhance the efficiency of risk asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 41 publications
1
11
1
Order By: Relevance
“…[34][35][36] In terms of the application value of DCE-MRI in assessing LVSI in cervical cancer, only few radiomics studies have been published, and the AUC value of the model ranged from 0.754 to 0.814. 18,19 In our study, a higher K trans value was significantly associated with the LVSI group, and k ep and V e showed no statistical difference between the LVSI group and non-LVSI group. For the standard Toft's model, tumor K trans was more sensitive to reflect tissue perfusion than other parameters.…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…[34][35][36] In terms of the application value of DCE-MRI in assessing LVSI in cervical cancer, only few radiomics studies have been published, and the AUC value of the model ranged from 0.754 to 0.814. 18,19 In our study, a higher K trans value was significantly associated with the LVSI group, and k ep and V e showed no statistical difference between the LVSI group and non-LVSI group. For the standard Toft's model, tumor K trans was more sensitive to reflect tissue perfusion than other parameters.…”
Section: Discussioncontrasting
confidence: 40%
“…Instead, the ECV fraction represents a quantitative assessment of the entire extracellular stromal space of the tumor, including blood and lymphatic vessels. Compared with previous MRI-based radiomics studies, [15][16][17][18][19][20] our results showed that ECV fraction, as a potential imaging parameter for predicting LVSI in cervical cancer, exhibited diagnostic value comparable to that of radiomics models. However, MRI-based radiomics models involve feature extraction and modeling of different MR sequences and combinations between sequences, so the whole process of radiomics is relatively complex and difficult to apply to clinical routine.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…Another study [ 50 ] in 2020 found that pretreatment albumin to fibrinogen ratio was significantly related to lymph node metastasis, depth of stromal infiltration, etc. Many studies focused on prediction for survival outcomes or a single PRF of cervical cancer based on clinical factors [ 51 , 52 , 53 ] and/or radiomic parameters [ 54 , 55 ]. However, no studies have made an attempt to predict three PRFs based on a series of clinically readily available blood markers.…”
Section: Discussionmentioning
confidence: 99%
“…However, as an invasive approach, it may also lead to excessive bleeding and inflammatory reaction in the local cervical tissue after surgery. Therefore, a non-invasive assessment of the coexistence of DSI and LVSI before initial treatment would also be of great value for cervical cancer patients in defining patient therapeutic strategies and evaluating prognosis or tailor follow-up intervals ( 16 ).…”
Section: Introductionmentioning
confidence: 99%